Answer:
x = -3
y = 0
Step-by-step explanation:
<u>Given</u><u> </u><u>equations</u><u> </u><u>:</u><u>-</u><u> </u>
<u>-x</u><u> </u><u>+</u><u> </u><u>2</u><u>y</u><u> </u><u>=</u><u> </u><u>3</u><u> </u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u> </u><u>(</u><u> </u><u>i</u><u> </u><u>)</u>
<u>2</u><u>x</u><u> </u><u>-</u><u> </u><u>3</u><u>y</u><u> </u><u>=</u><u> </u><u>-</u><u>6</u><u> </u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u> </u><u>(</u><u> </u><u>ii</u><u> </u><u>)</u>
<u>From</u><u> </u><u>(</u><u> </u><u>i</u><u> </u><u>)</u><u> </u><u> </u>
<u>-x</u><u> </u><u>+</u><u> </u><u>2</u><u>y</u><u> </u><u>=</u><u> </u><u>3</u><u> </u>
<u>-x</u><u> </u><u>=</u><u> </u><u>3</u><u> </u><u>-</u><u> </u><u>2</u><u>y</u><u> </u>
<u>x</u><u> </u><u>=</u><u> </u><u>2</u><u>y</u><u> </u><u>-</u><u> </u><u>3</u><u> </u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u> </u><u>(</u><u> </u><u>iii</u><u> </u><u>)</u>
<u>From</u><u> </u><u>(</u><u> </u><u>ii</u><u> </u><u>)</u><u> </u>
<u>2</u><u>x</u><u> </u><u>-</u><u> </u><u>3</u><u>y</u><u> </u><u>=</u><u> </u><u>-</u><u>6</u><u> </u>
<u>2</u><u>x</u><u> </u><u>=</u><u> </u><u>-</u><u>6</u><u> </u><u>+</u><u> </u><u>3</u><u>y</u><u> </u>
<u>
</u>
<u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u>.</u><u> </u><u>(</u><u> </u><u>iv</u><u> </u><u>)</u>
<u>Equating</u><u> </u><u>(</u><u> </u><u>iii</u><u> </u><u>)</u><u> </u><u>and</u><u> </u><u>(</u><u> </u><u>iv</u><u> </u><u>)</u>
<u>x</u><u> </u><u>=</u><u> </u><u>x</u><u> </u>
<u>
</u>
4y - 6 = -6 + 3y
4y - 3y = -6 + 6
y = 0
Putting value of y in ( iii )
x = 2y - 3
x = 2 ( 0 ) - 3
x = -3
Answer:
363
Step-by-step explanation:
0.66*550=363
Answer:
7 × 8
Step-by-step explanation:
7 number of students × 8 books each student has 7 × 8 = 56
Answer:
C. 25:4
Step-by-step explanation:
Total number of plants in Robert's garden = 8 + 4 + 16 + 22
= 50
Number of tomato plants in Robert's garden = 8
Ratio of total number of plants to the number of tomato plants = 50 : 8
Simplify
50 : 8 = 25:4
Answer:
Step-by-step explanation:
x²+24x+60=0
x²+24x+(24/2)²=-60+(24/2)²
(x+12)²=-60+144
(x+12)²=84